Evaluasi dan Redesain UI/UX pada Aplikasi Web Young on Top - Romadhoni, Muhammad Novid; Dirgahayu, Teduh (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
The youth community plays a vital role in supporting the career development of young people. In this context, the user interface (UI) and user experience (UX) of the Young On Top web application play a crucial role. The app experienced UI/UX-related challenges, such as issues with image size, information completeness, and layout inconsistencies, which directly impacted user confusion. The research method used involved a usability evaluation with the System Usability Scale (SUS) as well as interviews with participants, both new and experienced users. The redesign focused on improving the layout, color consistency, and adding important information on various pages such as registration, events, career, shop, and articles. These changes significantly improved the appearance and user experience. This research emphasizes the importance of evaluation and improvement in UI/UX to improve the quality and user satisfaction of the Young On Top web application. Thus, the alignment between users' needs and ease of interaction with the application can be optimally realized.